The concept of fractured rock-mass modeling using DFN-based statistical volume elements - Martin Lebeda; Petr Kabele (Acta Polytechnica CTU Proceedings, 2024)
The overall mechanical response of a fractured rock mass is, to a large extent, affected by naturally occurring fractures that exhibit sizes from millimeters to kilometers. Thus, in analysis of underground structures, such as tunnels, it is required that the fractures’ influence on the stress and deformation state in the vicinity of the structure is taken into account. In the present work, we examine the applicability of the statistical volume element (SVE) approach to determining the apparent stiffness tensor of an equivalent continuum representation of the fractured rock, which is then used in the framework of the finite element method. The equivalent continuum properties are determined by volume-averaging the effect of individual fractures that intersect the SVE, while the fractures are represented using the “parallel plate model”. Stochastically generated discrete fracture networks are used to represent the fractures’ geometry. Presently, we solve the problem linearly for an incremental change of the stress state. An application of the concept is demonstrated on simulation of tunnel excavation.